Assessing Cognitive Abilities of Patients With Shift Work Disorder: Insights From RBANS and Granger Causality Connections Among Resting-State Networks - Ning, Yanzhe; Li, Kuangshi; Zhang, Yong; Chen, Pei; Yin, Dongqing; Zhu, Hong; Jia, Hongxiao (Frontiers in Psychiatry, 2020)
Background: Numerous studies have confirmed that the long-term shift work is not only associated with increased health problems and acute effects on safety, but also with cognitive abilities. However, very little is known about effects of shift work on cognition-related brain resting-state networks. The aim of this study was to explore the effects of shift work disorder on granger causality connection among cognition-related brain networks. Methods: Thirty patients with SWD and 25 matched healthy subjects were recruited to undergo the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) and resting-state fMRI scanning. We employed independent component analysis (ICA) to extract resting-state brain networks, and granger causality analysis (GCA) to characterize the difference of granger causality connection among resting-state brain networks. Results: Compared with healthy subjects, patients with SWD showed declines on attention and immediate memory. Seven resting-state brain networks were identified, and patients with SWD showed more complex granger causality connections in comparison with healthy subjects. Two-sample t test results showed that there were significantly increased inflows from the anterior default mode network (aDMN) to between and sensorimotor network (SMN), and left frontoparietal network (LFPN) to salience network (SN). Conclusions: This study indicates that SWD impair cognitive performance, and the specific intrinsic brain granger causality connectivity among resting-state networks in SWD patients are affected after long-term shift works.